An Empirical Investigation on the Determinants of Interest Rate Spread of Commercial Banks in Bangladesh - Hossain, Akash; Lalon, Raad Mozib (International Journal of Economics and Financial Issues, 2024)
This paper aims to investigate the determinants or factors affecting the interest rate spread of private commercial banks in Bangladesh from 2013 to 2022. For the purpose of the study, the interest rate spread (IRS) of banks has been considered as a dependent variable while bank-specific factors and macroeconomic factors have been considered independent variables. Bank-specific factors are credit risk, bank size, operating cost ratio, liquidity risk, net interest income as a ratio of total income, capital adequacy ratio, and loan to deposit ratio while macroeconomic factors are Inflation and GDP. The Pooled Ordinary Least Square method (OLS), the Fixed Effect method (FE), the Random Effect method (RE), and the Generalized Least Square method (GLS) have been used to investigate the impact of the factors on interest rate spread. The results exhibit that bank-specific factors such as net interest income as a ratio of total income, and capital adequacy ratio are found to be statistically significant and positively impact the interest rate spread. In contrast, the results also exhibit that bank-specific factors such as bank size, operating expense ratio, and loan to deposit ratio are statistically significant and negatively impact the interest rate spread. Again, the results determine that the macroeconomic factor which is inflation found to be statistically significant and positively impacts the interest rate spread. The study’s findings will assist the banks’ regulatory body in formulating and developing strategies to maintain a satisfactory level of interest rate spread.